IMPLEMENTASI HUKUM TERHADAP TENAGA KERJA PEREMPUAN YANG BEKERJA PADA MALAM HARI (Studi Pada Pekerja Hotel Lee Bandar Jaya Lampung Tengah) - Irham, Irhammudin; Fikma Edrisy, Ibrahim (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2022)
Legal protection for workers is the fulfillment of basic rights inherent and protected by the constitution as regulated in Article 27 Paragraph (2) of the 1945 Constitution. Article 33 Paragraph (1) of the 1945 Constitution also states that the economy is structured as a joint effort of kinship. Violation of basic rights protected by the constitution is a violation of human rights. The sovereignty of a country is stated in the constitution which regulates the basics of the state and guarantees the rights and obligations of its citizens. Law Number 13 of 2003 concerning Manpower is one solution in protecting workers and employers regarding the rights and obligations of each party. Labor protection is regulated more clearly in Article 67 to Article 101 covering the protection of workers with disabilities, children, women, working hours, occupational safety and health, wages and welfare. In principle, the Manpower Law protects and regulates the rights and obligations of both workers and employers. In its implementation, various kinds of problems may arise that can harm the workforce itself, especially with regard to legal protection for female workers. Therefore, this study wants to reveal the form of legal protection that should be received by female workers who work at night. especially with regard to the legal protection of female workers. Therefore, this study wants to reveal the form of legal protection that should be received by female workers who work at night. especially with regard to the legal protection of female workers. Therefore, this study wants to reveal the form of legal protection that should be received by female workers who work at night.